The Changing Demography of Jewish London, Ontario: A Community Profile (2001–2021) - Margolis, Rachel (Canadian Jewish Studies / Études juives canadiennes)

(untitled) (Association for Canadian Jewish Studies / Association d’études juives canadiennes, 2025)
Canada’s Jewish population is growing slowly and aging rapidly. However, the national portrait may hide great variation across different contexts. This article examines Canada’s tenth largest Jewish community, that of London, Ontario. First, I highlight the size of the Jewish community according to different measures and how it’s changed between 2001 and 2021. Next, I examine the households in which London’s Jews live and what we can learn about changes in the characteristics of Jewish households and their members. This detailed analysis of the Canadian long-form census data highlights challenges and opportunities for local Jewish community leaders and institutions.